Impact of the COVID-19 Pandemic on Emergency Adult Surgical Patients and Surgical Services: An International Multi-center Cohort Study and Department Survey. Issue 6 (16th August 2021) - Winter Beatty, Jasmine; Clarke, Jonathan M.; Sounderajah, Viknesh; Acharya, Amish; Rabinowicz, Simon; Martin, Guy; Warren, Leigh R.; Yalamanchili, Seema; Scott, Alasdair J.; Burgnon, Elizabeth; Purkayastha, Sanjay; Markar, Sheraz; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objectives: The PREDICT study aimed to determine how the COVID-19 pandemic affected surgical services and surgical patients and to identify predictors of outcomes in this cohort. Background: High mortality rates were reported for surgical patients with COVID-19 in the early stages of the pandemic. However, the indirect impact of the pandemic on this cohort is not understood, and risk predictors are yet to be identified. Methods: PREDICT is an international longitudinal cohort study comprising surgical patients presenting to hospital between March and August 2020, conducted alongside a survey of staff redeployment and departmental restructuring. A subgroup analysis of 3176 adult emergency patients, recruited by 55 teams across 18 countries is presented. Results: Among adult emergency surgical patients, all-cause in-hospital mortality (IHM) was 3.6%, compared to 15.5% for those with COVID-19. However, only 14.1% received a COVID-19 test on admission in March, increasing to 76.5% by July. Higher Clinical Frailty Scale scores (CFS >7 aOR 18.87), ASA grade above 2 (aOR 4.29), and COVID-19 infection (aOR 5.12) were independently associated with significantly increased IHM. The peak months of the first wave were independently associated with significantly higher IHM (March aOR 4.34; April aOR 4.25; May aOR 3.97), compared to non-peak months. During the study, UK operating theatre capacity decreased by a mean of 63.6% with a concomitant 27.3% reduction in surgical staffing. Conclusion: The first wave of the COVID-19 pandemic significantly impacted surgical patients, both directly through co-morbid infection and indirectly as shown by increasing mortality in peak months, irrespective of COVID-19 status. Higher CFS scores and ASA grades strongly predict outcomes in surgical patients and are an important risk assessment tool during the pandemic.